Active noise and vibration control - Elliott, Stephen J. (Zielona Góra: Uniwersytet Zielonogórski)
Active control can reduce sound and vibration by destructive interference between the original, primary, field and the field generated by controllable secondary sources. It is most effective at low frequencies, for which the wavelength of the disturbance is comparable with the dimensions of the region being controlled. In this review paper the physical limitations of performance are first explored for vibration on a plate and sound in an enclosure, and the nature of the plant response is discussed in these two cases.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka